Effect of relationship closeness on group-induced choice shifts among chinese students - Park, Junsu; Kim, Do Yeong; Cheng, Cheng; Lee, Dongju (Journal of Ethnic and Cultural Studies, 2020)
Using hypothetical choice-dilemma scenarios, we examined the effect of relationship closeness on group-induced choice shifts in a sample of Chinese college students. Previous studies, which have shown an aversion to risk among Chinese students, have overlooked prior relationship closeness. This study attempts to fill the gap in the research by taking this factor into account. The study found that students shifted their choice toward greater risks when placed in groups composed entirely of individuals with high levels of closeness in their relationships than when they were alone. The implications of the findings are discussed from a Chinese Guanxi cultural perspective.
Keywords: Group decision-making; Guanxi; Relationship closeness; Risky shift